Business school-business interface and applied research - Ang, Bee Ling (2013)
In recent years, business practitioners and academic institutions around the world are becoming increasingly concerned about the rift between the business schools and business community. This thus spurred a series of studies to look into the reasons behind this problem and ways to narrow the gap.